Find the value of
Challenge: solve without calculus
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Start with n = 0 ∑ ∞ x n = 1 − x 1 which converges for ∣ x ∣ < 1 .
Differentiate: n = 0 ∑ ∞ n x n − 1 = ( 1 − x ) 2 1
Multiply by x : n = 0 ∑ ∞ n x n = ( 1 − x ) 2 x
Differentiate: n = 0 ∑ ∞ n 2 x n − 1 = ( 1 − x ) 3 1 + x
Multiply by x : n = 0 ∑ ∞ n 2 x n = ( 1 − x ) 3 x + x 2
Differentiate: n = 0 ∑ ∞ n 3 x n − 1 = ( 1 − x ) 4 1 + 4 x + x 2
Multiply by x : n = 0 ∑ ∞ n 3 x n = ( 1 − x ) 4 x + 4 x 2 + x 3 and since all of these steps maintained the same interval of convergence, this last series converges for ∣ x ∣ < 1 as well. In particular, we can set x = 3 1 on both sides of the equation to conclude
3 1 1 3 + 3 2 2 3 + 3 3 3 3 + ⋯ = n = 0 ∑ ∞ n 3 ( 3 1 ) n = ( 1 − 3 1 ) 4 ( 3 1 ) + 4 ( 3 1 ) 2 + ( 3 1 ) 3 = 8 3 3 = 4 . 1 2 5